ENGINE SIMULATOR DEVELOPMENT STRATEGY TO SUPPORT MECHANICAL ENGINEERING CORPS CADET TRAINING - I Made Jiwa; Mohamad Faikhul Himam; Rakhmad Susilo; Sutrisno Sutrisno (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
Study This is motivated by the holding of the Mechanical engineering corps Taruna training, which is less than optimal because space is not used optimally in the Sapudi Building Engine Simulator. The main objective in determining this strategy is to be able to maximize the available space in the Engine Simulator at the Sapudi Building. The research challenge is to determine the right strategy to optimize the engine simulator room in the Sapudi building to support the Mechanical engineering corps cadets. This research is quantitative and conducted by collecting respondents using a questionnaire with a purposive sampling technique. This study uses SWOT analysis. The first step is to create an IFAS and EFAS matrix with weights and determine the total score for the IFAS and EFAS variables. The second step is to develop strategies: SO, WO, ST, and WT. Further research shows that the advantages of the engine simulator room of Gedung Sapudi are designed like the KRI Sigma class. The drawback is that the Engine Simulator equipment included in the MCR (Machine Control Room) simulator is not yet mature in terms of quality and quantity. The results of this study are in the third quadrant, this condition is by minimizing existing internal problems and by maximizing existing opportunities through a review strategy to create something new. Keywords: SWOT Analysis, Engine Simulator, Borda Method